Protein Society Consumption Pattern Of Jambi Province - Adi Putra, Adi Putra; Deka, Deka Veronica (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2021)
Protein consumption for the community is very important and must be known, because improving nutritional status is the basis for the formation of quality, healthy, intelligent, productive, and independent human resources in an area. The level of public protein consumption, especially from beef products, is strongly influenced by the conditions of product supply and demand, because these indicators also affect prices and the level of inflation in general. For this reason, research needs to be done specifically to analyze the effect of price, inflation and per capita expenditure on the protein consumption pattern of the people in Jambi Province. The design of this research is a quantitative analysis of time series data for the period 2007-2018 which is further analyzed by Path Analysis. The results showed that there was no direct influence between the variable foodstuff inflation (IBM) and Beef Price (HDS) on Community Per Capita Expenditure (PBM), but PBM had an effect on Community Protein Consumption (KPM). The indirect effect between IBM on KPM through PPM and HDS on KPM through PPM has a significant effect. To maintain a healthy condition for protein consumption in Jambi Province, the government needs to take policies such as maintaining a stable condition of foodstuff inflation and beef prices in the market.